When gold stops glittering: corrosion mechanisms of René Lalique's Art Nouveau jewellery - Tissot, I. (2020)
ABSTRACT: Art Nouveau jewellery created by René Lalique is presently corroded. To identify the corrosion processes, Au-Ag-Cu alloys with compositions comparable to those used in the René Lalique’s jewellery were fabricated to be exposed to sulphide-containing environments. Using SEM-EDS, XRD, UV-Vis spectroscopy and ellipsometry, it was for the first time demon-strated that at the surface of tarnished Au alloys forms a corrosion film with a layer-by-layer structure. Considering the complex refractive indices of bulk Cu and Ag oxides and sulphides, a two-step corrosion mechanism was proposed. The formation of Cu-based compounds during the early corrosion stages is followed by the formation of Ag-based compounds. The thinness of the formed film, shown for one of the gold alloys to be of 80 nm, is due to a corrosion kinetics controlled by the presence of Au and by the formation of an Au-S self-assembled monolayer. The corrosion mechanism of gold alloys raises a new conservation challenge concerning the removal of nanometric layers.